The influence of Marangoni convection in engine oil base nanofluid with the impact of variable viscosity and viscous dissipation on infinite disk - Rehman, Ali; Khun, Ma Chau; Alotaibi, Hammad; İnç, Mustafa (Wiley-V C H Verlag Gmbh, 2024)
In this research work, we will investigate the influence of MC (Marangoni convection) in engine oil as base fluid with viscous dissipation and the influence of variable viscosity on an infinite disk. The flow system takes into account MC with influence of variable viscosity, convective boundary conditions, and viscous dissipation. Furthermore, for the sake of the present research paper, the graphical results of the temperature and velocity profiles are presented. To convert a collection of PDEs to NODEs, we applied appropriate transformations. We utilize the Homotopy analysis method to solve this set of equations. The effects of temperature and velocities on numerical perceptions involving Casson, magnetic, Schmidt number, thermophoresis, and Brownian motion input factors are shown. A physical description is used to simulate and evaluate the structures of flow features such as velocity and temperature profiles in response to changes in developing factors. It is hoped that this issue would contribute positively to improving the heat transformation ratio in order to satisfy the demands of the industrial and engineering sectors.
Keywords: Heat-Transfer Enhancement; Al2O3-Water Nanofluids; Water Nanofluid; Flow; Fluid